Theta rhythmicity governs human behavior and hippocampal signals during memory-dependent tasks - Ter Wal, Marije; Linde-Domingo, Juan; Lifanov, Julia; Roux, Frederic; Kolibius, Luca D.; Gollwitzer, Stephanie; Lang, Johannes; Hamer, Hajo; Rollings, David; Sawlani, Vijay; Chelvarajah, Ramesh; Staresina, Bernhard; et al. (Nature Communications, 2021)
Memory formation and reinstatement are thought to lock to the hippocampal theta rhythm, predicting that encoding and retrieval processes appear rhythmic themselves. Here, we show that rhythmicity can be observed in behavioral responses from memory tasks, where participants indicate, using button presses, the timing of encoding and recall of cue-object associative memories. We find no evidence for rhythmicity in button presses for visual tasks using the same stimuli, or for questions about already retrieved objects. The oscillations for correctly remembered trials center in the slow theta frequency range (1-5 Hz). Using intracranial EEG recordings, we show that the memory task induces temporally extended phase consistency in hippocampal local field potentials at slow theta frequencies, but significantly more for remembered than forgotten trials, providing a potential mechanistic underpinning for the theta oscillations found in behavioral responses.
CRIS-Team Scopus Importer:2021-12-17